2015
DOI: 10.4103/0976-3147.165424
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological, clinical and prognostic profile of childhood acute bacterial meningitis in a resource poor setting

Abstract: Background:Childhood bacterial meningitis is a neurologic emergency that continues to kill and maims children particularly in developing countries with poor immunization coverage.Objective:This study set out to assess the hospital incidence, pattern of presentation, etiologic agents, outcome and determinants of mortality among the children admitted with bacterial meningitis at the Wesley Guild Hospital (WGH), Ilesa.Patients and Methods:We carried out a retrospective review of admitted cases of bacterial mening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 7 publications
4
20
0
2
Order By: Relevance
“…Similar results were seen with 24% complications rate in a study published in Arch Dis Child 18. A few studies reported a much higher percentage of complications as compared to our study (39%, 42%) 3,10…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar results were seen with 24% complications rate in a study published in Arch Dis Child 18. A few studies reported a much higher percentage of complications as compared to our study (39%, 42%) 3,10…”
Section: Discussionsupporting
confidence: 91%
“…Our results were comparable with, studies done by Nhantumbo and Rajani in which CSF culture showed positivity in 7.3% and 7.2% respectively 12,13. A much higher percentage of 62.7% CSF culture positivity was reported in another study published in J Neurosci Rural Practice 3. A much high proportion (88% and 93.4%) of all meningitis cases in our study grew no bacterial pathogen.…”
Section: Discussionsupporting
confidence: 90%
“…Akut bakteriyel menenjit çocuklarda ve yenidoğan bebeklerde dünya genelinde önemli bir sağlık sorunu olduğundan erken tanı konarak acil tedavi edilmesi gerekmektedir (2,3,9) . Bazı gelişmekte olan ülkelerde, akut bakteriyel menenjitin mortalite oranı yeni ve etkili antibiyotikler bulunmasına rağmen hâlâ çok yüksektir (%16-32) (9)(10)(11) .…”
Section: Discussionunclassified
“…Bakteriyel menenjite sıklıkla neden olan etkenler arasında Streptococcus pneumoniae, Neisseria meningitidis ve Haemophilus influenzae type b'nin olduğu bildirilmektedir (2,3) . Ancak menenjit patojenlerinin prevalansı ve menenjit etiyolojisi, hastaların yaşı, coğrafi bölgeler, mevsim, popülasyonun belirli etkenlere karşı duyarlılığı, genetik yapı, sosyoekonomik koşullar ve lokal endemik faktörlere bağlı olarak göre değişkenlik gösterebilir (1) .…”
Section: Introductionunclassified
“…The study done by Levy C et al in 2014 5 showed mortality 10.6% after the introduction of routine vaccination. The study done by Kuti BP et al in 2015 6 in Nigeria, where vaccination is very poor showed commonest bacteria H. influenza type b and S. pneumonia while mortality was 27.2%. The studies done in various parts of Pakistan showed highly variable mortality from study to study ranging from 1.67-34%.…”
Section: Introductionmentioning
confidence: 97%